ANALYSIS OF E-SERVICE QUALITY AND E-RECOVERY SELLER SERVICE ON ONLINE REPURCHASE INTENTION WITH E-LOYALITY AS A MEDIATION VARIABLE ON TIKTOK SHOP - Wiladatulqhairi Qhairi; Fenisi Resty; Mayroza Wiska (Universitas Islam Lamongan, 2024)
This study was conducted to determine and analyze the influence of E-service quality and E-recovery seller service on online repurchase intention with the E- loyalty variable as a mediating variable on TikTok Shop. The results of this study show the influence of E-Service Quality on E-loyalty, there is an influence of E-recovery seller service on E- loyalty, there is an influence of E-service quality on online repurchase intention, there is an influence of E-recovery Service Quality on Online Repurchase Intention, there is an influence of E-loyalty on online repurchase intention, there is an indirect influence of E-service quality on online repurchase intention through E-loyalty as a mediating variable, there is no indirect influence of E- service quality on online repurchase intention through E-loyalty as a mediating variable. It is hoped that TikTok will improve and pay more attention to the quality of e-service quality, e-recovery services so that TikTok buyers or visitors will increase so that consumers are loyal and make repeat purchases on the TikTok Shop application